Effect of Insulin-Transferrin-Selenium (ITS) supplementation on development rate and quality of bovine embryos in vitro - Acosta Lobo, Mariano Eliécer (2024)
The aim of this study was to evaluate the effect of Insulin-Transferrin-Selenium (ITS) supplementation in embryo culture on the blastocyst rate and embryo quality. The bovine zygotes obtained by in vitro maturation (MIV) and fertilization (IVF) were transferred to Evolve medium in 4 groups (T1: Without ITS supplement; T2: ITS the first 48 h of culture (CIV1): T3: ITS after day 2 of culture (CIV2), T4: ITS during all culture time (CIV1 + CIV2). All procedures were performed at 38.5 °C, 5% CO2 and 90% relative humidity. The cleavage and blastocyst rates were determined at 48 h and day 8 of culture. The total cell number and the production of reactive oxygen species (ROS) in the expanded blastocysts were determined by staining the nucleus with Hoechst and the oxidation of the fluorescent probe dichlorodihydrofluorescein diacetate (H2DCFDA). The T4 cultured embryos presented the highest rate of blastocysts (32.6%) and total cell number (145.6) compared to the control group without STI (26.2% and 98.6, respectively; p<0.05). Likewise, the production of ROS in T4 blastocysts was lower (p<0.05) than that obtained in the other study groups. The results show that the addition of the ITS supplement throughout the embryo culture time has beneficial effects on the percentage of blastocysts and embryo quality, assessed by the number of total cells and the production of ROS.